P–300 Metformin: new therapeutic approach for endometriosis-associated infertility. (6th August 2021) - Net. Cerqueira, A C; Rodrigues, A R; Lamas, S; Gouveia, A M; Almeida, H; Neves, D
Abstract: Study question: Could endometriosis-associated infertility be mitigated by metformin? Summary answer: Metformin treatment restored fertility to control rates in endometriosis-induced mice that present lower fertility. No effect was observed on sham-operated mice. What is known already: Endometriosis is a gynaecological disorder characterized by ectopic vascularized endometrial tissue growth, mainly in pelvic cavity, which provokes pain and infertility. Corroborating observations in women, endometriosis decreases oocyte quality and pregnancy success in rodents, without affecting the number of ovulations, resorption rate and fetal weight. Thus, animal models of endometriosis constitute a valuable tool to elucidate the pathophysiology of the disease and putative pharmacological therapies. Metformin is widely used for diabetes type–2 treatment, reducing glucose, oxidative stress and inflammation. Due to its antioxidant properties, metformin has shown to induce regression of endometrial implants in a rat model of endometriosis. Study design, size, duration: B6CBA/F1 female mice were randomly divided in groups and subjected to treatment: 1-Endometriosis (n = 20); 2-Sham-operated (n = 12); 3-Endometriosis with metformin (n = 20); 4-Sham-operated with metformin (n = 20). Endometriosis was surgically induced by heterologous transplantation of endometrium from one donor in receptors from the same strain mice. Implants were confirmed and monitored by ultrasound. 50mg/kg/day of metformin was orally administrated during 3 months to Groups 3 and 4. Half of mice in each group were mated to fertility study. Participants/materials, setting, methods: Endometriomas were monitored at 3 timepoints during the experiments. Biometric parameters of mice and number of implantation sites, fetuses and fetal weight were recorded. Fertility rates were assessed by the average number of fetuses in each group. Histological characterization of ovary, uterus, endometriomas, and peritoneal tissue at the implant site was performed by Hemathoxylin & Eosin (H&E) staining. Statistical study among groups was carried out and significant differences were considered for student t-test < 0.05. Main results and the role of chance: A decrease of 30% of fertility rate was verified in mice with endometriosis (p = 0, 01); treatment with metformin was able to revert this decrease (p = 0, 04). Interestingly, no differences in fertility were found in sham-operated mice under metformin treatment relatively with those of group 2 (p = 0, 16). Although the number of absorptions observed in mice of the endometriosis group was higher, no statistical difference was reached comparatively with other groups. No biometrical differences were found between mice with endometriosis receiving metformin and those that do not receive the drug. Regarding H&E staining we verified that endometriomas showed histologically resemblances to uterus. Moreover, endometriomas from mice without treatment with metformin were dark brown, recalling for human endometriomas called "chocolate" cysts, while the endometriomas from mice who were treated with metformin were visually clearly. We postulate that these findings owes to a metformin-mediated decrease of oxidative imbalance and inflammatory response, induction of regression of endometriomas and regulation of oestrogen secretion. Limitations, reasons for caution: Extrapolation of data from animal models to human needs caution, considering that endometriosis pattern differs between species. Also, further investigation, focused in identification of molecular targets of metformin and molecular pathways activated in endometriosis, is needed and in course. Wider implications of the findings: With these results, we indicate metformin as a novel and safe strategy to mitigate endometriosis-related oxidative stress and indeed could be used as a valid pharmacological approach to ameliorate endometriosis-associated infertility. Trial registration number: Not applicable